ANALISA SLUM TOURISM SEBAGAI ALAT PROPAGANDA PARIWISATA INDONESIA (STUDI KASUS : PROVINSI DKI JAKARTA TAHUN 2008-2016) - Wahyu Dilla Ramadhany; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research is a contemporary study which analyzes slum tourism as a propaganda media for Indonesian tourism especially in Jakarta Province in 2008 until 2016. Slum tourism is well-known as a new phenomenon in global tourism, where this tourism represents a unique and unusual form of tourism which invites tourists to visit a rural or slum areas which is inhabited by poor and marginalized people. It‟s indeed opposite with Indonesian Tourism‟s slogan it should reflect the beauty of the nature of Indonesia, so slum tourism is claimed as a propaganda media which could change the image of Indonesian Tourism.This research uses postmodernism as the perspective by Richard Ashley. By applying contructivism theory by Alexander Wendt and level analysis is Interest Groups. This research uses qualitative method and library research for references by collecting data from books, journals, articles, and news that come from various medias. And applying the questions to the parties who are involve in this research through media.In spite of being a propaganda media, the fact is slum tourism can be a complete package of tourism where the tourists do not only visit but also do social activities and charity. Besides, slum tourism also gives advantages for Indonesia, especially DKI Jakarta where it could increase the country‟s income as well as province‟s income with the increasing number of tourists which follows the tour. This research represents that the perspective of tourism does not only point out on commercial sector, however, can cause humanity side.Keywords : tourism, slum tourism, propaganda